Substantiation for the development of a new dosage form from tansy flowers in chemical and pharmacological studies - A. I. Khusainova; E. N. Zaitseva; A. V. Dubishchev; A. V. Kurkina (Сеченовский вестник)
The pharmacological and pharmacognostical investigations were carried out. The necessity for development the composition of tansy flowers syrup was substantiated. The technology of production of tansy flowers syrup was demonstrated there. By means of thin layer chromatography the technique of qualitative analysis of syrup was developed to determine tiliolin, which is the main diagnostic flavonoid. Quantitative analysis of total content of flavonoids calculated as cynaroside was developed by the method of differential spectrophotometry at an analytical wavelength of 400 nm. The pharmacological studies were worked out to determine the impact on the excretory function of the kidneys of rats of tansy flowers syrups on the basis of fructose and sorbite at a dose of 50 μl/kg. It was revealed that tansy flowers syrup on the basis of fructose most eff ectively promotes diuresis due to tubular effect, while the tansy flowers syrup on the basis of sorbitol, with less expressed diuretic properties, leads to an increase in creatininuresis and saluresis, as due to the stimulation of glomerular filtration, and due to inhibition of tubular reabsorption. Administration the tansy tincture at a dose of 15 g/kg did not lead to death of animals. It proved that this medicine belongs to the class IV toxicity (low hazardous substances) according to GOST 12.1.007–76.